2015
DOI: 10.1038/onc.2015.439
|View full text |Cite
|
Sign up to set email alerts
|

CHIP-mediated degradation of transglutaminase 2 negatively regulates tumor growth and angiogenesis in renal cancer

Abstract: The multifunctional enzyme transglutaminase 2 (TG2) primarily catalyzes cross-linking reactions of proteins via (γ-glutamyl) lysine bonds. Several recent findings indicate that altered regulation of intracellular TG2 levels affects renal cancer. Elevated TG2 expression is observed in renal cancer. However, the molecular mechanism underlying TG2 degradation is not completely understood. Carboxyl-terminus of Hsp70-interacting protein (CHIP) functions as an ubiquitin E3 ligase. Previous studies reveal that CHIP d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…CHIP is reported to have a tumor suppressor function in renal [52], gastric [53,54], colorectal [55] and breast cancers [56,57] with an unknown mechanism. We had earlier shown that CHIP is able to restore wild-type function to mutant p53 thus causing hypoxic tumor regression [48].…”
Section: Discussionmentioning
confidence: 99%
“…CHIP is reported to have a tumor suppressor function in renal [52], gastric [53,54], colorectal [55] and breast cancers [56,57] with an unknown mechanism. We had earlier shown that CHIP is able to restore wild-type function to mutant p53 thus causing hypoxic tumor regression [48].…”
Section: Discussionmentioning
confidence: 99%
“…These effects are reversed by TG2 knockdown . The ubiquitination system also influences TG2 function, as TG2 level is reduced following modification by CHIP (carboxyl‐terminus of hsp70‐interacting protein), an E3 ubiquitin ligase, and CHIP knockdown is associated with elevated TG2 and aggressive cancer (Figure B). This may be a unique response in renal cancer cells, as we did not observe CHIP regulation of TG2 in squamous cell carcinoma (Eckert, unpublished).…”
Section: Tg2 In Tumor Typesmentioning
confidence: 99%
“…A, The glioma reference is . B, The renal cancer references are . C, The prostate cancer reference is …”
Section: Tg2 In Tumor Typesmentioning
confidence: 99%
“…The peculiar biochemistry of this enzyme as well as its capacity to interact with the main proteins involved in the regulation of proteostasis suggests that TG2 plays a key role in this process. For example, among the TG2 intracellular partners, many are molecular chaperones, such as the heat‐shock proteins HSP70, HSP27, HSP90 as well as co‐chaperone from the DNAjs and the BAG families . Indeed, recent compelling evidence places TG2 within the regulation of main pathways controlling the proteome homeostasis as autophagy, proteasome and exosomes .…”
Section: Introductionmentioning
confidence: 99%